Jesus’ Responses to Power Tussle in Mark 10:35-40 and the Recent Nigerian Presidential Party Primaries in Comparative Context - Ogbole, Friday Abu; Ikyernum, Ephraim Sachia; Obijole, Olubayo O. (Kashere Journal of Politics and International Relations, 2023)
And the two sons of Zebedee, namely James and John went to request for positions of honour in Jesus’ coming kingdom, the same way a Vice President went to inform his boss of his desire to take over from him in 2023. On the other hand, the Vice President’s political godfather and presidential hopeful would remark that none of his sons is grown enough to declare for president. The resultant effect of the foregoing drama will be a sharp division within the disciples and the ruling party’s camp; with arguments and counter arguments being laid down for the latter that the Vice President was not right to have declared for that office, or he was, knowing fully that his godfather was equally eyeing the same position. This is going to become a tug of war, if the situation is not properly handled by Jesus and the Nigerian president. The two leaders’ responses are therefore going to ensure that their camp remains united and not broken. This paper thus, seek to use the approach of Jesus and the Nigerian President in handling the issue of power tussle to address the problem of conflict in succession from different aspects of national life, be it the monarchy, church, government, education and familyThe work adopts histo-critical and comparative method of enquiry as well as made use of the media and other relevant literature to carry out the research.